MASJID DAN FUNGSINYA DALAM PEMBINAAN AKHLAK DI KECAMATAN BEUTONG KABUPATEN NAGAN RAYA - Adam Sani (Universitas Teuku Umar, 2018)
The purpose of this study to determine the optimization of the function of mosques in the guidance of morals in Beutong District Nagan Raya District. This research is a type of qualitative research. namely a research procedure that produces descriptive data in the form of written or oral words of people and behavior that can be observed. This research will describe and analyze the mosque and its function in moral guidance in Beutong Sub-district, Nagan Raya District. So the specification of this research is through a descriptive research approach that aims to describe the systematic, accurate facts, and characteristics about a particular field. This research was conducted in Beutong Sub-district, Nagan Raya District. Technique of collecting data in research with observation method, documentation and interview or also called primary data, and secondary data obtained through books, articles, electronic media related to research problem while to analyze data in this research done by study, categorization, perform tabulation of data and or combine evidence to answer research questions. The results showed that the optimization of mosque function in the guidance of morality in Beutong Sub-district of Nagan Raya District is as an institution of non-formal religious education, Role as instrument, Role as facilitator, Role as mobilizer, Role as a container of human resources development, Role as agent of development of society .Keywords: Mosque, coaching, Morals